RICTOR/mTORC2 affects tumorigenesis and therapeutic efficacy of mTOR inhibitors in esophageal squamous cell carcinoma - Zhaoming Lu; Xiaojing Shi; Fanghua Gong; Shenglei Li; Yang Wang; Yandan Ren; Mengyin Zhang; Bin Yu; Yan Li; Wen Zhao; Jianying Zhang; Guiqin Hou (Elsevier, 2020)
Dysregulation of mTORC1/mTORC2 pathway is observed in many cancers and mTORC1 inhibitors have been used clinically in many tumor types; however, the mechanism of mTORC2 in tumorigenesis is still obscure. Here, we mainly explored the potential role of mTORC2 in esophageal squamous cell carcinoma (ESCC) and its effects on the sensitivity of cells to mTOR inhibitors. We demonstrated that RICTOR, the key factor of mTORC2, and p-AKT (Ser473) were excessively activated in ESCC and their overexpression is related to lymph node metastasis and the tumor-node-metastasis (TNM) phase of ESCC patients. Furthermore, we found that mTORC1/ mTORC2 inhibitor PP242 exhibited more efficacious anti-proliferative effect on ESCC cells than mTORC1 inhibitor RAD001 due to RAD001-triggered feedback activation of AKT signal. Another, we demonstrated that down-regulating expression of RICTOR in ECa109 and EC9706 cells inhibited proliferation and migration as well as induced cell cycle arrest and apoptosis. Noteworthy, knocking-down stably RICTOR significantly suppresses RAD001-induced feedback activation of AKT/PRAS40 signaling, and enhances inhibition efficacy of PP242 on the phosphorylation of AKT and PRAS40, thus potentiates the antitumor effect of RAD001 and PP242 both in vitro and in vivo. Our findings highlight that selective targeting mTORC2 could be a promising therapeutic strategy for future treatment of ESCC.